2011
DOI: 10.1007/s10059-011-0135-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Arabidopsis Transcription Factor Families Revealed Extensive Capacity for Cell-to-Cell Movement as Well as Discrete Trafficking Patterns

Abstract: In plants, cell-to-cell communication is pivotal for the orchestration of cell fate determination, organ development, and the integration of whole plant physiology. One of the strategies for intercellular communication uses symplasmic communication channels, called plasmodesmata (PD). These PD establish unique cytoplasmic channels for the intercellular exchange not only of metabolites and small signaling molecules, but also of regulatory proteins and RNAs to allow for local orchestration of development and phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 47 publications
3
31
0
Order By: Relevance
“…This extends findings described in previous reports that CPC-Dendra2 (a photoconvertible fluorescent protein) was able to move isodiametrically within the root epidermis (Wu et al, 2011) and that fluorescence signal was detected in all epidermal cells in EGL3p:CPC-GFP plants (Kurata et al, 2005a). Furthermore, we showed that CPC/CPC-GFP expressed in the root ground tissue or in the stele led to CPC-GFP accumulation in the root epidermis and alterations in epidermal cell fate specification, consistent with a report that fluorescence signal was detected in the epidermis and the stele when CPC-mCherry was expressed in root ground tissue (Rim et al, 2011). From this, we conclude that the CPC protein is able to move out from inner tissue layers of the root to the epidermis to affect cell fate specification.…”
Section: Movement Of Cpc Protein Within and Between Tissues In The Desupporting
confidence: 74%
“…This extends findings described in previous reports that CPC-Dendra2 (a photoconvertible fluorescent protein) was able to move isodiametrically within the root epidermis (Wu et al, 2011) and that fluorescence signal was detected in all epidermal cells in EGL3p:CPC-GFP plants (Kurata et al, 2005a). Furthermore, we showed that CPC/CPC-GFP expressed in the root ground tissue or in the stele led to CPC-GFP accumulation in the root epidermis and alterations in epidermal cell fate specification, consistent with a report that fluorescence signal was detected in the epidermis and the stele when CPC-mCherry was expressed in root ground tissue (Rim et al, 2011). From this, we conclude that the CPC protein is able to move out from inner tissue layers of the root to the epidermis to affect cell fate specification.…”
Section: Movement Of Cpc Protein Within and Between Tissues In The Desupporting
confidence: 74%
“…This contrasts with results for GFP-CPC in Arabidopsis, where movement between cells of the fusion protein was observed (Kurata et al, 2005;Digiuni et al, 2008). However, in that case, a specific amino acid motif was required for movement to occur, and a gated transport mechanism through plasmodesmata was suggested (Kurata et al, 2005;Wang et al, 2008;Rim et al, 2011). Notably, however, CPC variants lacking the motif were capable of intercellular movement in roots, suggesting passive diffusion as a secondary transport mechanism (Rim et al, 2011).…”
Section: Mybx Is a Repressormentioning
confidence: 71%
“…However, in that case, a specific amino acid motif was required for movement to occur, and a gated transport mechanism through plasmodesmata was suggested (Kurata et al, 2005;Wang et al, 2008;Rim et al, 2011). Notably, however, CPC variants lacking the motif were capable of intercellular movement in roots, suggesting passive diffusion as a secondary transport mechanism (Rim et al, 2011). An alternative interpretation of the biolistic data is that MYBx prevented AN11 from moving; however, this is unlikely given that the MYBs are not effective binders of WDR proteins (Figure 1; Payne et al, 2000;Baudry et al, 2004Baudry et al, , 2006Chiu et al, 2010;An et al, 2012).…”
Section: Mybx Is a Repressormentioning
confidence: 98%
“…Given that the size exclusion limit of PD in the root meristem is suggested to be around 60 kD (Crawford and Zambryski, 2001;Rim et al, 2011), AHL4-GFP (72 kD) might move between cells in a targeted manner. To gain a better understanding of AHL4 movement, the coding region of AHL4 was fused with tandem yellow fluorescent proteins (YFPs; 3x or 4xYFP) driven by the CRE1 promoter and introduced into an ahl4-1 mutant.…”
Section: Movement Of Ahl4 Is Critical For the Boundary Between The Xymentioning
confidence: 99%